Clinically Oriented Pharmacology Exercises and Innovative Evaluation System - Rakesh Chandra Chaurasia (Technological Innovation in Pharmaceutical Research Vol. 11, 2021)
Medical science is very vast discipline concerned with the life of human being; Thus, skills, communication and decision-making abilities are important tools for medical knowledge. In current scenario of modern life, students are pressurized from every corner of society. Economic burden, lack of friendly environment, senior and peer group pressure, single parents, drug addiction and love affair are common issues during college life. Insecurity of job after completion of education will create future financial fear. Pharmacology is an essential subject of medical science with marked clinical potential. The prescription and pharmacotherapy of any clinical discipline is nothing but Pharmacology. This is the fact that we are always linked with our old tradition, but time has been changed now and needs upgradation of old presentation. This chapter presented some of upgraded and innovative efforts in context to practical, written and oral examination.